2010
DOI: 10.1038/ijo.2010.76
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a low-energy diet on sexual function and lower urinary tract symptoms in obese men

Abstract: Objective: Abdominal obesity and type 2 diabetes mellitus are associated with erectile and urinary dysfunction in men. The extent to which sexual function and lower urinary tract symptoms (LUTSs) are improved by weight loss remains unclear. Subjects: We compared the effects of 8 weeks of a low-calorie diet using meal replacements (Kicstart) on insulin sensitivity, plasma testosterone levels, erectile function (measured by the five-item version of the International Index of Erectile Function, IIEF-5), sexual de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
83
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 36 publications
(72 reference statements)
12
83
1
1
Order By: Relevance
“…Few randomized clinical studies have specifically evaluated the impact of diet and physical activity on testosterone levels in obese men. The results of these studies are essentially conflicting: some of them showed an increase of testosterone (26,27,28,29,30,31,32,33,34), others showed no change (35,36,37,38,39), and one small study has shown even a decrease in testosterone levels (40). Similarly, in the last 10 years, several trials have evaluated the impact of bariatric surgery on testosterone levels in men generally, showing an increase in testosterone levels (41,42,43,44,45,46,47,48).…”
Section: Introductionmentioning
confidence: 97%
“…Few randomized clinical studies have specifically evaluated the impact of diet and physical activity on testosterone levels in obese men. The results of these studies are essentially conflicting: some of them showed an increase of testosterone (26,27,28,29,30,31,32,33,34), others showed no change (35,36,37,38,39), and one small study has shown even a decrease in testosterone levels (40). Similarly, in the last 10 years, several trials have evaluated the impact of bariatric surgery on testosterone levels in men generally, showing an increase in testosterone levels (41,42,43,44,45,46,47,48).…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, testosterone therapy promotes metabolically favourable changes in body composition (Wittert et al 2003) associated with moderate decreases in insulin resistance (Grossmann 2011), whereas, conversely ADT given to men with PCa leads to visceral fat gain and increased insulin resistance . In addition, weight loss can lead to substantial increases in testosterone Endocrine-Related Cancer (2012) 19 F47-F62 www.endocrinology-journals.org levels, especially in morbidly obese men (Khoo et al 2010), and this increase in testosterone is proportional to the amount of weight lost (Grossmann 2011). Thus, testosterone has complex interactions not only with prostate biology, but also direct relationships with PCa metabolic risk factors such as diabetes, obesity and the MetS.…”
Section: Relationship Between Sex Steroids and Diabetesmentioning
confidence: 99%
“…This suggests that weight loss can lead to genuine reactivation of the gonadal axis by reversal of obesity-associated hypothalamic suppression. Weight loss can also improve quality of live and sexual function in obese men, but whether this is causally related to the associated increase in testosterone levels is not known (Khoo et al 2010). …”
Section: Testosterone and Insulin Resistance: A Bilateral Relationshipmentioning
confidence: 99%